Pesticide Safety Miniposter: Pest Control Vehicle Safety - Rebecca W. Baldwin; Stephanie K. Larrick Hill; Philip Koehler; P. A. Mitola; J. C. Medley (EDIS)
Do you need to train your employees about vehicle safety while transporting pesticides? This poster introduces safety concepts when transporting pesticides on a vehicle and alerts new pest control technicians to the pest control vehicle regulations of the Florida Department of Agriculture. The poster has quick response (QR) codes linked to short, online videos that take the technicians though six steps of maintaining a safe and legal service vehicle. This poster will serve as a valuable training and refresher tool. Designed by R.W. Baldwin, S.K. Hill, Philip Koehler, P.A. Mitola, and J.C. Medley, and published by the UF Department of Entomology and Nematology, August 2012.